ANALISIS PENGARUH CITRA MEREK, KEPERCAYAAN MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN UNTUK MEMBELI MIE INSTAN MIE SEDAP (Studi Kasus Pada Konsumen Mie Sedap kota Medan) - Franadita, Dwi; Silalahi, Purnama Ramadani (Universitas Labuhanbatu, 2021)
In the current era of globalization, advertising board is a discipline that has significance in the business world, given the absence of innovation trend setting in various fields requires every individual or organization () to consistently compete to achieve what is aspired. the goal, in particular to obtain the benefits of the ideal. with the cost a little. Be an innovator in the market can be estimated with the recognition of the market and the situation during a state of emergency and the difficulty in the whole world. Indeed, become a winner was difficult, especially at the level of the customer who is easily tempted to try or switch brands or different goods. The organization should have the option to compete and follow their business in a climate of strict business, items of new competitors,kemajuanmekanis, legislation or government settings that continues to grow quickly.